Examining the factors that affect structural repetition in question answering. - Chia, Katherine; Hetzel-Ebben, Hannah; Adolph, Maxwell; Amaral, Madison; Arriaga, Maynor; Booth, Holly; Boudreau, Victoria; Carpenter, Jennifer; Cerra, Carolina; Clouden, Megan; Cryderman, Jacob; Darji, Rida; et al. (Memory & Cognition, 2020)
We present two experiments that examine structural priming in the single-trial phone-call paradigm introduced by Levelt and Kelter (Cognitive psychology, 14 (1), 78-106, 1982). Experimenters called businesses and asked either What time do you close? or At what time do you close? Participants were more likely to produce a prepositional response (At 7 o'clock vs. 7 o'clock) following a prepositional question than following a non-prepositional question. Experiments 1 and 2 attempted to strengthen the priming effect by having the experimenters engage in a brief interaction with the participant before asking the What time...? question. The interactions did not reliably affect the observed priming effect. An analysis across experiments demonstrated that the priming effect found in this paradigm is generally smaller than the average structural priming effect (as reported in Mahowald, James, Futrell, & Gibson, Journal of Memory and Language, 91, 5-27, 2016), but within the range of the effects that are observed in different structural priming paradigms.